(untitled) (Research, Society and Development, 2021)
This work aimed to propose and apply a case study through the theme "hair straightening". For this, we used a Case-Based Learning (CBL) approach associated with the syllabus of a Metabolism Fundamentals course offered to students of the 5th semester of a teacher training degree course. As a data collection instrument, a questionnaire was used in which students should choose the correct alternatives and justify their answers to solve the proposed case. Data analysis included a qualitative approach, based on the categorization of the answers presented in the instrument. The results of this work show that the students had difficulty in solving the activity. This finding may be due to students’ lack of experience in developing activities with this approach, or because they did not understand that they could point out several alternatives to solve the case. This research is expected to contribute to the study about CBL, and it also assists in the Biochemical concepts understanding, investigate in this study.